Effect of Surface State on Acid Rain Corrosion Resistance of T6 6005A Aluminum Alloy by BT-FSW Joint. (January 2020) - Qin, Zhiheng; Xu, Hongji
Abstract: The test sample was 5 mm thick artificial aging 6005A aluminium alloy profile, which was butted by BT-FSW. This work aimed to analyse the effect of surface state on corrosion resistance of welded joints in acid rain environment based on acetate ssalt spray test (CASS), polarization curve and EIS impedance test, combined with SEM scanning and EDS energy spectrum. The results showed that the corrosion rate of pre-welded polished joints was high at the initial stage of salt spray corrosion, and the corrosion rate of both joints were equal at the later stage of corrosion, higher than that of base metal. The best preservation of corrosion morphology was THAZ, followed by nugget zone and HAZ, and the pitting degree of base metal was the most serious. The polarization curves of the polished joints before 30 min corrosion were located at the lower right of the image, and its self-corrosion current density in the nugget zone showed the worst corrosion resistance. The corrosion resistance of the pre-welded polished joint increased after 336 hours of corrosion, the corrosion breakdown potential and self-corrosion current were not significantly different from those of the unpolished joints. The fitting curves of the two kinds of joints had similar dual capacitance arc resistance characteristics and the impedance parameters in EIS, and the electrochemical corrosion resistance of the two joints were weaker than that of the base metal.